Investigation of the Prognostic Significance of Vasculogenic Mimicry and Its Inhibition by Sorafenib in Canine Mammary Gland Tumors - Prado, Maria Carolina Mangini; Macedo, Sofia de Almeida Losant; Guiraldelli, Giulia Gumiero; de Faria Lainetti, Patricia; Leis-Filho, Antonio Fernando; Kobayashi, Priscila Emiko; Laufer-Amorim, Renee; Fonseca-Alves, Carlos Eduardo (Frontiers in Oncology, 2019)
Canine mammary gland tumour (CMT) is one of the most important tumours in intact female dogs, and due its similarity to human breast cancer (BC), it is considered a model in comparative oncology. A subset of mammary gland tumours can show aggressive behaviour, and a recurrent histological finding is the presence of vasculogenic mimicry (VM). VM is a process in which highly aggressive cancer cells fuse, forming fluid-conducting channels without endothelial cells. Although VM has been described in canine inflammatory carcinoma, no previous studies have investigated the prognostic and predictive significance of VM in CMT. Thus, this research aimed to investigate the prognostic significance of VM in vivo and the capacity of sorafenib to inhibit VM in vitro. VM was identified in situ in formalin-fixed paraffin-embedded CMT samples (n= 248) using CD31/PAS double staining. VM was identified in 33% of tumours (82/248). The presence of VM was more strongly related to tumour grade than to histological subtype. Patients with positive VM experienced shorter survival times than dogs without VM (P<0.0001). Due to the importance of the VEGF-A/VEGFR-2 autocrine feed-forward loop in epithelial tumours, we investigated the association between VEGF-A and VEGFR-2 expression by neoplastic tumour cells and the associations of VEGF-A or VEGFR-2 expression with VM. Among the VM-positive samples, all (n=82) showed high scores (3 or 4) for VEGF-A and VEGFR-2, indicating that VM was a common finding in tumours overexpressing VEGF-A and VEGFR-2. Thus, we cultured two CMT primary cell lines with VM abilities (CM9 and CM60) in vitro and evaluated the anti-tumoural effect of sorafenib. The CM9 cell line showed a half maximal inhibitory concentration (IC50) of 2.61 µM, and the CM60 cell line showed an IC50 of 1.34 µM. We performed a VM assay in vitro and treated each cell line with an IC50 dose of sorafenib, which was able to inhibit VM in vitro. Overall, our results indicated that VM was a prognostic factor for dogs bearing CMT and that sorafenib had an inhibitory effect on VM in CMT cancer cells in vitro.